The Role of the Indonesian Tobacco Farmers Association in Mobilizing Resistance to Tobacco Regulation in Temanggung Regency - Bagas Makhrus Wicaksono; David Efendi; Alam Mahadika (Journal of Local Government Issues (LOGOS), 2021)
This research focuses on the mobilization of the role carried out by the movement Indonesian Tobacco Farmers Association (APTI) of Temanggung Regency is to thwart the implementation of Non-Smoking Areas (KTR) that will be applied in Temanggung. They  pressing for Regulation of the Ministry of Agriculture Republic Indonesia Number 23 of 2019 About Technical Recommendations For Tobacco Imports to be realized immediately, the allocation of Tobacco Excise Revenue Sharing Fund (DBH- CHT) returning to farmers is raised, and the rejection of the increase in retail selling price and excise that rises significantly. By using social movement theory with qualitative descriptive methods where primary data is obtained in direct interviews with respondents and sources who have valid and relevant information to find out the actual problems experienced by tobacco farmers, especially in Temanggung Regency. Then the authors use secondary data to strengthen the validity of the data obtained by the researcher. The results of this study illustrate that tobacco control regulations are not entirely for public health but are used as a pretext in the nicotine market share. So far, APTI has carried out various ways and strategies so that national-scale regulations can be changed or removed. In addition to tobacco control regulations, there are also classes of tobacco farmers in Temanggung to give birth to local capitalization and make the tobacco trade chain longer.